From noose to needle : capital punishment and the late liberal state - Kaufman-Osborn, Timothy V. (Timothy Vance), 1953- (University of Michigan Press, 2002)
Discusses the dilemmas of the relationship between the liberal state and capital punishment.
Keywords: Capital punishment -- United States.; Capital punishment -- Political aspects.; Hanging -- United States.; Lethal injection (Execution) -- United States.; Liberalism.; Free enterprise.; Peine de mort -- États-Unis.; Peine de mort -- Aspect politique.; Pendaison -- États-Unis.; Injection létale (Exécution capitale) -- États-Unis.; Libéralisme.; liberalism.; SOCIAL SCIENCE -- Penology.; HISTORY -- General.; Free enterprise; Capital punishment; Capital punishment -- Political aspects; Hanging; Lethal injection (Execution); Liberalism; United States; Todesstrafe; Geschichte; USA